The unseen body : a doctor's journey through the hidden wonders of human anatomy - Reisman, Jonathan (Flatiron Books, 2021)
"In this fascinating journey through the human body and across the globe, Dr. Reisman weaves together stories about our insides with a unique perspective on life, culture, and the natural world. Jonathan Reisman, M.D.-a physician, adventure traveler and naturalist-brings readers on an odyssey navigating our insides like an explorer discovering a new world with The Unseen Body. With unique insight, Reisman shows us how understanding mountain watersheds helps to diagnose heart attacks, how the body is made mostly of mucus, not water, and how urine carries within it a tale of humanity's origins. Through his offbeat adventures in healthcare and across the globe, Reisman discovers new perspectives on the body: a trip to the Alaskan Arctic reveals that fat is not the enemy, but the hero; a stint in the Himalayas uncovers the boundary where the brain ends and the mind begins; and eating a sheep's head in Iceland offers a lesson in empathy. By relating rich experiences in far-flung lands and among unique cultures back to the body's inner workings, he shows how our organs live inextricably intertwined lives-an internal ecosystem reflecting the natural world around us. Reisman offers a new and deeply moving perspective, and helps us make sense of our bodies and how they work in a way readers have never before imagined"--